Penal and legal permissibility of gender reassignment surgery – present status and suggested regulation - Kubiak, Rafał (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
Under the present Polish law there are no provisions to regulate directly reassignment surgery. However, it is indirectly accepted as legal because administrative and civil law activities in files of the birth and death register much depend on it. In other jurisdictions conditions of such medical surgery are not determined, either. From the penal law point of view the surgery may result in meeting a definition of a crime of heavy damage to one’s health. In consequence a person may be deprived of procreation capacity which corresponds to a description of an act punishable under art. 156 § 1 p. 1 of the Polish penal code. This study is an analysis of the problem and suggests legal potential solutions to the issues discussed here.